Could 1, 3 dimethylamylamine (DMAA) in food supplements have a natural origin?. Issue 2 (3rd September 2012) - Di Lorenzo, Chiara; Moro, Enzo; Dos Santos, Ariana; Uberti, Francesca; Restani, Patrizia
<x xml:space="preserve">Abstract</x> 1, 3 dimethylamylamine or methylexaneamine (DMAA) is a synthetic pharmaceutical patented in the 1940s as a nasal decongestant which can be used as a recreational stimulant. Alleged to occur in nature, DMAA has become a widely used ingredient in sports food supplements, despite its status as a doping agent and concerns over its safety. There is now some doubt as to whether it can be sourced naturally or whether it actually occurs naturally at all. The presence of DMAA was investigated by high performance liquid chromatography (HPLC) in extracts of the leaves and stems of four geranium species and of three well‐known cultivars. The amounts of DMAA in commercial geranium (Pelargonium graveolens) oil and the leading sports supplement which uses the ingredient were also measured. DMAA was not found in any of the leaves or stems or in the commercial geranium oil included in this study. Approximately 30 mg per daily dose was found in the food supplement. Therefore, the amount of DMAA found in the supplement is most unlikely to have been sourced in nature, and it must be concluded that synthetic DMAA, known to be capable of causing severe adverse physiological effects, has been added. Copyright © 2012 John Wiley & Sons, Ltd.